Mul Meyaj Tía U Betá Jump’el Kaj: Working Together to Build a Community in Puuc Archaeology - Kenneth E. Seligson; Manuel Chi Nah (Heritage, 2020)
This paper explores specific challenges that archaeologists face when attempting to involve a broader community of local stakeholders in cultural heritage research. We combine our perspectives as a US-based archaeologist and a local community member in a discussion of practical approaches for promoting more equitable research collaborations in the Puuc region of the northern Maya lowlands. The format of the paper includes a blend of dialogue, narrative, and analysis. First, we evaluate the importance of engaging in social interactions outside of the fieldwork setting and examine the limitations to full-coverage community participation. Next, we discuss the structural barriers discouraging greater local interest in cultural heritage research. We assess the potential of linguistic education and digital conservation programs for encouraging broader-scale engagement with knowledge production. Finally, we highlight the importance of employment by archaeological research projects as the critical factor influencing local participation in heritage-related activities. Barring immediate structural changes to the socio-economy of the Yucatán, the most significant way to promote local involvement in cultural heritage projects is for archaeologists and community members to work together to try to secure funding for more sustainable employment opportunities.